Pengaruh Likuditas, Leverage, Profitabilitas, dan Aktivitas terhadap Return Saham Studi pada Perusahaan Food and Beverage yang terdaftar di BEI periode 2015-2020 - Ratih Kusumawardhani; Putri Dwi Cahyani; Gendro Wiyono (Reslaj : Religion Education Social Laa Roiba Journal, 2022)
This study aims to determine the effect of liquidity (CR), leverage (DER), profitability (ROE), and activity (TATO) on stock returns. The type of research used is a quantitative approach. The sampling criteria used a purposive sampling technique with a sample of 9 Food and Beverage companies listed on the Indonesia Stock Exchange (IDX) for the 2015-2020 period. In this study, the data were analyzed using the multiple regression analysis method and the classical assumption test which was processed using the SPSS version 25 program. . The results showed that liquidity (CT) had a negative and significant effect on stock returns, leverage (DER) had no significant effect on stock returns, profitability (ROE) had a positive and significant effect on stock returns, and activity (TATO) had no significant effect on stock returns. . The results of the study simultaneously show that the variables of liquidity, leverage, profitability, activity have a positive and significant effect on stock returns. From the results of the research above, it is expected that the company will always maintain the company's performance, especially liquidity (CR) because liquidity (CR) can have a negative and significant influence on stock returns. Meanwhile, investors and people who want to invest their capital need to consider the company's profitability (ROE) because profitability (ROE) can have a positive and significant impact on stock returns so that in the decision-making process it needs to be considered. Keywords: Liquidity (CR), Leverage (DER), Profitability (ROE), Activity (TATO), Stock Return